The New Guide to Stability Design Criteria for Metal Structures - Johnston, Bruce G. (Engineering Journal, 1976)
The purpose of this report is to review the 3rd Edition of the "CRC Guide" for readers of the AISC Engineering Journal. There has always been a close and special relationship between the American Institute of Steel Construction and the Column Research Council, officially renamed the "Structural Stability Research Council" in March, 1976. The new name reflects the broadened coverage of the Council that has been gradually achieved over the past 32 years of its history. The name of the 3rd Edition of the "CRC Guide", published in April of 1976, has likewise been changed as indicated in the above title of this review. In 1961 the AISC Advisory Committee on Specifications made major revisions in the AISC Specification for the Design, Fabrication and Erection of Structural Steel for Buildings. These included extensive improvements in clauses pertaining to the buckling behavior of laterally unsupported beams, columns, and beam-columns. These changes were needed because of the introduction at that time of higher strength steels and by the corresponding possibility of achieving greater economy and correctness in the design of steel structures. The AISC Advisory Committee on Specifications turned to the Column Research Council to provide backup and substantiation for the new specification it was about to introduce. It was at that time, too, that architectural concepts in the construction of steel buildings were breaking sharply away from the traditional types of the past. Simplified procedures that had evolved through successful past experience were no longer adequate for the new steels and the new, varied shapes of current construction practice.